All but a Pose? Unlikeable Heroines in Contemporary Fiction by Women - Szołtysek, Julia (Text Matters: A Journal of Literature, Theory and Culture, 2025)
The present research grows out of an engagement with emerging trends in contemporary fiction by young women authors whose works frequently feature unrelatable and ultimately unlikable female narrators and/or protagonists. Within the framework provided by dissociative feminism and nascent Femcel/Femceldom Studies, I investigate the portrayal in fiction of female protagonists who are young and talented, but who nevertheless struggle with strong self-destructive tendencies. In the first part of the article, devoted to Conversations with Friends (2017) by Sally Rooney and The Lesser Bohemians (2016) by Eimear McBride, I enquire whether the two authors’ young protagonists fall into the trap of repeating their own patterns, or whether they manage to overcome the self-delusion that smart and sensitive types like themselves are prone to wallow in, both physically and mentally. The second part turns to Lisa Taddeo’s and Eliza Clark’s troubled narrators in their respective debuts, Animal (2021) and Boy Parts (2020), offering a comparison of the two novels in terms of their treatment of predatory, cunning, and deceptive female protagonists. In an attempt to dissect the empathy and support gained among readerships by unconventional female protagonists, I also explore the ways in which misogynistic narratives about female depravity are appropriated and reclaimed by female authors who then “recycle” them for their own purposes, daring to challenge the patriarchal order.